Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1051/0004-6361:20053396
|View full text |Cite
|
Sign up to set email alerts
|

The nature of ultraviolet spectra of AG Pegasi and other symbiotic stars: locations, origins, and excitation mechanisms of emission lines

Abstract: A detailed study of ultraviolet spectra of the symbiotic star AG Peg has been undertaken to derive the atomic excitation mechanisms and origin of formation for the lines common in symbiotic systems. More than 600 emission lines are observed in spectra from IUE, HST and FUSE of which 585 are identified. Population mechanisms and origin of formation are given for a majority of those lines. Based on the understanding of the AG Peg spectra IUE data of 19 additional symbiotic stars are investigated and differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…Zanstra temperatures are in the range 90 kK to 110 kK. Eriksson et al (2006) determined WD wind velocities of 120 to 150 km s −1 based on a re-analysis of the IUE high resolution spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Zanstra temperatures are in the range 90 kK to 110 kK. Eriksson et al (2006) determined WD wind velocities of 120 to 150 km s −1 based on a re-analysis of the IUE high resolution spectra.…”
Section: Introductionmentioning
confidence: 99%
“…P-Cygni profiles from UV spectroscopy indicate fast outflows and multiple line components indicate various wind domains as emission sources (Eriksson et al 2006). At the same time as the white dwarf seems to accrete matter from the red giant wind at 8.1 × 10 −8 M per year, the overall system loses matter with a speed of 3.3 × 10 −7 M per year (Skopal 2005).…”
Section: Eg Andmentioning
confidence: 99%
“…Eriksson et al (2006) analyzed over 600 UV emission lines in spectra of symbiotic stars and gave origins of formation as well as identifying the atomic process accounting for the population of the corresponding upper level for a majority of the lines. They concluded that a large fraction of relatively narrow Fe II lines present in UV spectra of symbiotic stars are formed by photo excitation by accidental resonance (PAR), a process originally described by Bowen (1935), and sometimes called Bowen-fluorescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if symbiotic stars are smaller by many magnitudes than the AGN, radiation processes observed in the symbiotic stars could also occur in AGNs. One process with a very strong impact on the UV spectrum of symbiotic stars is photoexcitation by accidental resonance (PAR) (Eriksson et al 2006). The most striking effect of the PAR process in symbiotic stars is the large number of strong Fe II fluorescence lines in the 2300−2800 Å region.…”
Section: Introductionmentioning
confidence: 99%